Failure of ETeMS: The Teaching Courseware Factor? - Latiff Azmi, Mohd Nazri; Maniam, Manhendren (2013)
This study was carried out in response to the announcement of the reversal of the ETeMS policy (English in the Teaching of Mathematics and Science) which had been practiced by teachers in Malaysia since 2003. The Ministry of Education took a drastic approach in gradually halting this controversial policy for several related reasons, namely the poor performance of students and teachers in applying the policy and also political pressure by Malay language activists. The main objective of the study is to investigate whether or not the application of CALL (Computer Assisted Language Learning), in this case is the application of teaching courseware, is one of the contributing factors to the failure of ETeMS. This study also investigated teachers’ perception of the teaching courseware implementation in ETeMS. Fifty primary school key - personnel teachers of Mathematics and Science were involved in answering the questionnaire because they were experienced and fully involved in the policy implementation. The findings showed that teachers were not committed to use the courseware for several reasons. However, the teaching courseware is not the major contributing factor to the failure of ETeMS.